Reproduction Performance of Local Cock (Gallus domesticus) Primary Organ with Gonadotrophin Hormone Induction - Tagama, T Rahman (ANIMAL PRODUCTION, 2003)
A research was conducted to know the effect of gonadohrophin hormone induction to reproduction performance of local chicken (Gallus domesticus). The materials used for this research were 24 heads of local chicken, with average aged of 8 months, and weight ranged from 1.9 to 2.0 kg. This research using Pregnant Mareâs Serum Gonadotrophin (PMSG) hormone. Laboratory experiments with 4 groups of treatment were employed in this research; each group was repeated 6 times (6 heads), with hormone dose level as treatment. The group PO treated by 0 IU. hormone PMSG (control); P1 by 20 IU.; P2 by 40 IU.; and P3 by 60 IU. Completely randomized design was applied as the basic design. Furthermore, to observeÂ  difference within variables, analysis of variance and Duncan Multiple Range Test (DMRT) were performed. Result showed that there was a significantly different (P<0.01) between the treatment of groups P0, P1, P2, and P3 on testes relative weight, testes volume, and total gamete cells. The average of testes relative weight for each treatment groups respectively were as follows: P0 = 0.73%; P1 = 0.76%; P2 = 1.01%; and P3 = 1.05%. The average of testes volume respectively were as follows: P0 = 0.68 ml; P1 = 0.69 ml; P2 = 0.93 ml; and P3 = 1.03 ml. The average of total gamete cells respectively was as follow: P0 = 31.50 cells; P1 = 30.29 cells: P2 = 51.52 cells; and P3 = 75.48 cells. (Animal Production 5(2): 87-92 (2003)Â Key Words : PMSG, Testes Relative Weight, Testes Volume, Leydig Cells